Spatial and temporal dimensions of fire activity in the fire‐prone eastern Canadian taiga - Erni, Sandy; Arseneault, Dominique; Parisien, Marc-André; Bégin, Yves (Global Change Biology, 2017)
The forest age mosaic is a fundamental attribute of the North American boreal forest. Given that fires are generally lethal to trees, the time since last fire largely determines the composition and structure of forest stands and landscapes. Although the spatiotemporal dynamics of such mosaics has long been assumed to be random under the overwhelming influence of severe fire weather, no long‐term reconstruction of mosaic dynamics has been performed from direct field evidence. In this study, we use fire length as a proxy for fire extent across the fire‐prone eastern Canadian taiga and systematically reconstruct the spatiotemporal variability of fire extent and fire intervals, as well as the resulting forest age along a 340‐km transect for the 1840–2013 time period. Our results indicate an extremely active fire regime over the last two centuries, with an overall burn rate of 2.1% of the land area yr−1, mainly triggered by seasonal anomalies of high temperature and severe drought. However, the rejuvenation of the age mosaic was strongly patterned in space and time due to the intrinsically lower burn rates in wetland‐dominated areas and, more importantly, to the much‐reduced likelihood of burning of stands up to 50 years postfire. An extremely high burn rate of ~5% yr−1 would have characterized our study region during the last century in the absence of such fuel age effect. Although recent burn rates and fire sizes are within their range of variability of the last 175 years, a particularly severe weather event allowed a 2013 fire to spread across a large fire refuge, thus shifting the abundance of mature and old forest to a historic low. These results provide reference conditions to evaluate the significance and predict the spatiotemporal dynamics and impacts of the currently strengthening fire activity in the North American boreal forest. -- Keywords : Extreme weather Fire overlaps Fire size Fire‐free intervals Fuel feedback Natural range of variability Predictability of boreal forest‐age mosaics ...